Investigating the functional significance of presynaptic tau in ageing and disease. (20th December 2022) - Groves, Emily E; Sung, Katherine; Flores‐Dominguez, Diana; Pollack, Saskia J; Croft, Cara L; Golde, Todd E; Hanger, Diane P; McAdam, Robyn; Giese, Karl Peter; Noble, Wendy
Abstract: Background: Synaptic dysfunction is an early pathological feature of neurodegenerative disease and is a close correlate of cognitive decline. Modified tau mislocalises to the synaptic compartment in disease, where some forms of tau interact with synaptic proteins and disrupt synapse function. This study seeks to further explore synaptic tau accumulation, and the impact on synaptic health and tau release, during ageing and tauopathy progression. Method: Post‐mortem Brodmann area 9 (BA9) pre‐frontal cortex from control or Braak stage I‐VI tissues were obtained. Formalin‐fixed paraffin‐embedded sections were subject to immunohistochemistry. Total lysates, cytosolic and synaptoneurosome fractions were isolated for western blotting, imaging and analysis of synaptic protein interactions. Organotypic brain slice cultures were prepared from P9‐10 wild‐type mice and Tau35 mice in which a disease‐associated tau fragment is expressed. In addition, some wild‐type slices were transduced with AAV2/TM8‐WT‐htau0N4R‐EGFP (WT) or AAV2/TM8‐P301L/S320F‐htau0N4R‐EGFP. Slices were cultured for 21‐28 DIV. Total lysate, cytosolic, and synaptoneurosome fractions were isolated for western blot, immunocytochemistry, or immunoprecipitation. Culture medium was used for tau sandwich ELISA. Result: We observed progressive neurodegenerative changes, including the accumulation of sarkosyl‐insoluble tau, in organotypic brain slices expressing Tau35 and mutant (AAV‐expressed) human tau. Mislocalisation of phosphorylated and aggregated tau to the synaptic fraction in the tauopathy slice models mirrors, at least in part, changes observed in postmortem AD brain. Tau mislocalisation was associated with significant loss of specific pre‐synaptic proteins in Tau35 mice and AD brain. Mutant AAV‐expressed tau, but not WT AAV‐expressed tau, interacts with specific presynaptic vesicle proteins. Furthermore, alterations in basal tau release from slices was observed when disease‐like tau was expressed. Conclusion: Slice cultures from mice in which disease‐associated tau is expressed at physiological levels (Tau35) or in which mutant tau is virally induced recapitulate key elements of human tauopathy. These long‐term brain slice cultures allow sensitive characterisation of presynaptic alterations that occur early in tauopathy. These models are now being used to determine if interactions between tau and pre‐synaptic proteins are essential for tau‐mediated synaptic dysfunction and/or tau release.